An Accurate Method of Designing and Performing Individual‐Specific Genioglossus Advancement. (22nd October 2016) - Liu, Stanley Yung‐Chuan; Huon, Leh‐Kiong; Zaghi, Soroush; Riley, Robert; Torre, Carlos
Abstract : There is too much individual patient variation in mandibular anatomy for any single described genioglossus advancement technique to be used consistently. Virtual surgical planning allows surgeons to design genioglossus osteotomy that captures the structures of interest. Intraoperative osteotomy and positioning guides mitigate known risks of the procedure while maximizing the reproducibility and efficacy of the procedure. In this report, we demonstrate the protocol step by step as it had been used on 10 patients, and we highlight 3 clinical scenarios that exemplify its utility.